Opportunities to Study and Modify the Experience of Foreign Internet Promotion (Eurasian Journal of Research, Development and Innovation, 2022)
This article talks about the possibilities of studying and modifying the experience of foreign internet promotion. The article focuses on the analysis of the most effective methods of the spiritual promotion process tested in the world experience. Propaganda focuses on the analysis of approaches to the use of various sources to achieve success in the process of dissemination of information. World experience related to the propaganda process, its application and types are classified in various aspects of society's life.